2022
DOI: 10.1177/02666669221114867
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of post custodial management of digital records in Botswana laid bare

Abstract: This paper presents the challenges of post custodial management of digital records in the context of Botswana. This is a qualitative study which used a focused review literature supplemented by interviews with seven (7) purposively selected records management experts. The study has revealed that the post-custodial management of digital records is a challenging vocation in Botswana. Such challenges include poor information and communication technology infrastructure, lack of capacity for digital records managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Lack of standards to support digital preservation is a major challenge in Africa (Osedo 2013). This study revealed lack of standards for the management and preservation of digital records in Botswana (Porogo & Kalusopa 2021;Mosweu & Bwalya 2022). Standards provide an essential framework for organisations to benchmark their activities (Chikomba et al 2020).…”
Section: Adoption Of Standardsmentioning
confidence: 92%
See 3 more Smart Citations
“…Lack of standards to support digital preservation is a major challenge in Africa (Osedo 2013). This study revealed lack of standards for the management and preservation of digital records in Botswana (Porogo & Kalusopa 2021;Mosweu & Bwalya 2022). Standards provide an essential framework for organisations to benchmark their activities (Chikomba et al 2020).…”
Section: Adoption Of Standardsmentioning
confidence: 92%
“…This e-government practice generates digital records that need proper management, like their paper counterparts. However, digital records preservation faces numerous challenges such as lack of preservation policies; inadequate policy framework for digital preservation; gaps in human resources in terms of knowledge, funding difficulties, skills, poor awareness of digital preservation, lack of collaboration, and competencies to drive digital material preservation; and the absence of standards for digital preservation (Kalusopa & Zulu 2009;Adu & Ngulube 2016;Ngoepe & Saurombe 2016;Mosweu & Bwalya 2022;Porogo 2022). The resultant digital records generated by implemented business systems face preservation challenges, which may be a disadvantage to organisations that pursue cloud computing for its goodness.…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Yee Goh (2002, p. 1) notes that archival legislation in several Commonwealth countries, including the UK, Canada and Singapore, lacks consistency and, as such, is unable to assist archivists in ensuring the management and preservation of records throughout the full span of their life cycle. Kalusopa et al (2021), Mosweu (2021) and Mosweu and Bwalya (2022) report that Botswana had legislative framework focusing on electronic records, but the shortfall was that legislation did not cover all records management matters pertaining to e-records management including the process of records capturing, interval for retention and preservation custody, as such legislations were produced or created with limitations.…”
Section: Literature Reviewmentioning
confidence: 99%